2021
DOI: 10.1021/acs.organomet.1c00592
|View full text |Cite
|
Sign up to set email alerts
|

Expedient Synthesis of Bis(imidazolium) Dichloride Salts and Bis(NHC) Complexes from Imidazoles Using DMSO as a Key Polar Additive

Abstract: A general approach for the synthesis of bis(imidazolium) dichloride salts from imidazoles and dichloroalkanes is reported. Typical limitations of this reaction for the formation of methylene-bridged derivatives are addressed herein through the use of an excess CH2Cl2 in the presence of DMSO as a polar cosolvent, significantly improving conversion rates presumably via stabilization of the initial SN2 transition state. The method was also shown to be applicable to the formation of bis(pyridinium) dichloride salt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…While NHC–Au­(III) complexes are expected (and probably formed first), these can be reduced to the thermodynamic NHC–Au­(I) complex over time . Additional studies have showed that multidentate bis- or tetrakis-imidazolium salts can lead to the formation of [NHC 2 –AuCl 2 ]­Cl and [NHC 4 –AuCl 2 ]Cl complexes using similar reaction conditions. , Consequently, due to the high NHC ligand local concentration in the polymer precursors, such oligo-NHC Au complexes could be obtained and need to be considered as well. Accordingly, before proceeding with any type of AEM tests, it is necessary to ascertain the type of complexes obtained within each of the metallopolymers.…”
Section: Resultsmentioning
confidence: 99%
“…While NHC–Au­(III) complexes are expected (and probably formed first), these can be reduced to the thermodynamic NHC–Au­(I) complex over time . Additional studies have showed that multidentate bis- or tetrakis-imidazolium salts can lead to the formation of [NHC 2 –AuCl 2 ]­Cl and [NHC 4 –AuCl 2 ]Cl complexes using similar reaction conditions. , Consequently, due to the high NHC ligand local concentration in the polymer precursors, such oligo-NHC Au complexes could be obtained and need to be considered as well. Accordingly, before proceeding with any type of AEM tests, it is necessary to ascertain the type of complexes obtained within each of the metallopolymers.…”
Section: Resultsmentioning
confidence: 99%
“…Synthesis of 3,3′-Methylenebis(1-methyl-1H-imidazol-3-ium) Dichloride. The preparation of the dicationic ionic liquid (C 1 (MIm) 2 Cl 2 ) was performed with little changes from the method described by Penn et al 29 In a round-bottom flask with 1.15 mL of DMSO, 1-methylimidazole (20 mmol) and CH 2 Cl 2 (60 mmol) were added together. The reaction was conducted under stirring at 100 °C for 24 h. The resulting white insoluble precipitate was washed three times with diethyl ether to remove the DMSO and any trace of unreacted imidazole.…”
Section: Methodsmentioning
confidence: 99%
“…1-Benzyl-1H-imidazole 5b and most alkenes were acquired from commercial suppliers and were used without further purification. Here, 1-mesityl-1H-imidazole 5a was synthesized according to published procedures [46]. The 1 H and 13 C NMR spectra were obtained at 25 • C in CDCl 3 on a Bruker AV 400 NMR spectrometer (Bruker Co., Faellanden, Switzerland), in which the chemical shifts (δ in ppm) were established with respect to CHCl 3 .…”
Section: Instruments and Reagentsmentioning
confidence: 99%